The effectiveness of acceptance and commitment therapy on communication skills of female students of high school - Fatemi, Vahideh Alsadat; Shafie Abadi, Abdollah; Khalatbari, Javad; Farhangi, Abdolhasan (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of admission and commitment therapy on communication skills of female high school students. Methods: The research method was quasi-experimental with a pre-test, post-test design with a control group with a 2-month follow-up phase. In this study, the statistical population was female high school students in Tehran in the academic year 2019-20. Using simple random sampling method, 30 of them were divided into two groups of experimental and control (15 people in each group). The experimental group underwent 12 90-minute sessions of acceptance and commitment therapy sessions adapted from Peterson, Efert, Fingold, and Davidson (2009); But the control group did not receive any intervention and remained on the waiting list. The Revised Communication Skills Questionnaire Queendom (2004) was used to collect information. The analysis of information obtained from the implementation of questionnaires was performed through SPSS software version 24 in two descriptive and inferential sections (analysis of covariance, one-way analysis of variance and Bonferroni post hoc test). Results: The results showed that acceptance and commitment treatment in the post-test and follow-up stages compared to the control group had a significant effect on message perception (F=6.37, P=0.004), emotion regulation (F=8.62, P<0.001), listening (F=4.57, P=0.017), insight into communication (F=4.04, P<0.001), assertiveness (F=9.16, P<0.001) has teenage girls. Conclusion: Based on the results of the present study, it can be said that acceptance and commitment therapy can be used as therapeutic methods to improve communication skills of adolescent girls in educational and medical settings.